Pemikiran Islam Wasathiyah Prof. Habib Abdullah Bin Muhammad Baharun - Ahmad Hanif Fahruddin; Tohirin (Universitas Islam Lamongan, 2025)
The attitude of moderation of Prof. Dr. Habib Abdullah Baharun is contained in his book entitled